Frequency and nature of recorded childhood immunization-related errors in Greece. - Petridou, E; Kouri, N; Vadala, H; Dalamaga, M; Sege, R (J Toxicol Clin Toxicol, 2004)
BACKGROUND: While routine immunizations are very safe, their administration to healthy children requires minimization of immunization programmatic errors. In order to estimate the incidence and ascertain the nature of reported immunization errors in the Greek childhood population, we have undertaken a study using data from the National Poison Information Center in Greece, which also has the responsibility to address medication-induced errors. METHODS: All immunization errors concerning children and reported to the National Poison Information Center during the 2-yr period 1999-2000 were retrieved and the conditions of their occurrence were examined. The incidence of reported errors was calculated under the assumption that during each year 100,000 children are born in Greece, and during their childhood they receive a total of about 20 immunization doses of all childhood immunizations. RESULTS: There were 40 immunization errors reported, corresponding to a reported incidence of about 11 per million immunization doses. Of these errors, 20 concerned OPV, 13 DTP, 5 MMR, 1 Haemophilus influenza and 1 Hepatitis B immunizations. In 12 instances an erroneous route was used (out of which 11 concerned OPV), whereas overdose was documented in 13 instances (out of which 8 concerned OPV). The third most common error was administration of DTP instead of the recommended Td vaccine. No adverse patient outcomes were reported. CONCLUSIONS: In Greece, reported errors in immunization practice are relatively rare. Packaging modifications (about one in three errors in this study) of the OPV and DTP could further reduce their incidence.
Keywords: Adolescent; Child; Child, Preschool; Drug Overdose; Drug Packaging; Greece; Humans; immunization; Immunization Programs; Infant; Medical Records; Medication Errors; Poison Control Centers